ON A FAIR VERDICT - S. G. Ol'kov (Russian Journal of Economics and Law)
RETRACTION:Date of retraction: 13.03.2017Reason for retraction: Duplicate publication in several editions Additional information about the causes of retraction:The article "On a fair verdict", written by Sergey Gennadyevich Ol'kov, Doctor of Law, Professor of Surgut State University, is a duplicate publication. Information from public databases allowed the editors of the journal "Actual Problems of Economics and Law" to identify a violation of publication ethics. An article by the said author, containing essentially the same data and conclusions, was published in another publication: Forensic Library. Science Magazine. 2014. No. 6 (17). pp. 151-156. (http://elibrary.ru/item.asp?id=22511771). An article by S.G. Ol'kov “On a fair verdict”, published in the scientific journal “Actual Problems of Economics and Law”. 2014. No. 2 (30). pp. 203-209. Retracted with the consent of the author, editor-in-chief and publisher. The Editorial Board of the Journal, when publishing scientific research materials, bases its performance on the rules of publication ethics observed by the Editorial Board members, reviewers and authors. According to these rules, the author shall guarantee that the article is published for the first time and was not previously published or submitted to another journal. From the editor-in-chief and publisher of the author Ol'kov S.G. it was pointed out that such actions were inadmissible and a decision was made to remove the article from the site elibrary.ru and the site of the journal.